Perancangan Sistem Informasi Pemasaran Perumahan Berbasis Web - Julia Dwi Saputri; Ariansyah; Fajriyah (PPPM Institut Teknologi Pagar Alam, 2026)
Muara Cipta Baru Housing is currently still conducting marketing manually through the distribution of brochures and word-of-mouth, resulting in limited marketing reach and less effective information delivery. To improve information dissemination and make things simpler for prospective buyers to acquire data regarding house types, prices, and locations, a marketing system of information that is accesible widely and quickly is required. This study attempts for create a web-based on housing advertising system of information utilizing the prototype technique, which allows the system development process to be carried out interactively through stages of requirement communication, rapid design, user evaluation, and iterative improvements until a system that meets needs is prodused.